Changes of Nutritional Value of Steamed Lumi-Lumi Fish (Harpodon nehereus) Flour - Safrida Safrida; Cukri Rahma; Maiza Duana (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Lumi-lumi fish (Harpodon nehereus) or known as Bombay duck is a type of commercial demersal fish in the city of Meulaboh. Aceh. This fish can live all year round. The availability of this fish is quite large but often it is not appropriately used. it is only processed traditionally. Lumi-lumi has been reported to have good nutritional content. The objective of this study was to identify the nutritional content of fish in Lumi-lumi. In this study. Lumi-lumi fish was conducted into 2 treatments: steamed fish and non-steamed fish. Identification of nutritional content was carried out on fish that had been processed into flour. In this study. the yield of Lumi-lumi fish meal in the non-steamed treatment was 10.23%. and in the steamed treatment. it was 10.57%. The nutritional value of Lumi-lumi fish meal protein which was steamed was significantly (p<0.05) higher than that which was not steamed. namely 13.32 ± 0.48% and 9.50 ± 0.70%. respectively. However. the fat content was lower in the steamed treatment. which was 12.56 ± 1.18%. compared to not steamed. which was 14.24 ± 0.96%. Significant moisture and ash content (p<0.05) were lower in the steamed treatment than in the non-steamed treatment. Meanwhile. the fiber content was significantly (p<0.05) higher in the steam treatment. Therefore. steamed lumi-lumi fish has a higher protein content. Fat content following SNI 01-2715-1996 fish flour quality standards.